2022
DOI: 10.1172/jci155478
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenesis requires Ang2/Tie/PI3K signaling for VEGFR3 cell-surface expression

Abstract: Vascular endothelial growth factor C (VEGF-C) induces lymphangiogenesis via VEGF receptor-3 (VEGFR3), encoded by the most frequently mutated gene in human primary lymphedema. Angiopoietins (Angs) and their Tie receptors regulate lymphatic vessel development and mutations of the ANGPT2 gene were recently found in human primary lymphedema. However, the mechanistic basis of Ang2 activity in lymphangiogenesis is not fully understood. Here we used gene deletion, blocking antibodies, transgene induction and gene tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 70 publications
(150 reference statements)
3
35
0
Order By: Relevance
“…We here show that tie1 mutant zebrafish embryos display severe lymphatic defects in the head and trunk vasculature, in addition to the previously reported cardiac and blood vascular phenotypes including impaired brain angiogenesis, reduced CCV width, and impaired caudal vein plexus formation (Carlantoni et al, 2021). Interestingly, the FCLV, which seem to have a comparable function to collecting lymphatic vessels, is affected in tie1 mutant zebrafish embryos, while Tie1;Tie2 double deletion in mice leads to defective postnatal collecting lymphatic vessel development (Korhonen et al, 2022). Further studies will be required in both mice and fish to determine to what extent Tie signalling affects LEC specification, proliferation, and survival.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We here show that tie1 mutant zebrafish embryos display severe lymphatic defects in the head and trunk vasculature, in addition to the previously reported cardiac and blood vascular phenotypes including impaired brain angiogenesis, reduced CCV width, and impaired caudal vein plexus formation (Carlantoni et al, 2021). Interestingly, the FCLV, which seem to have a comparable function to collecting lymphatic vessels, is affected in tie1 mutant zebrafish embryos, while Tie1;Tie2 double deletion in mice leads to defective postnatal collecting lymphatic vessel development (Korhonen et al, 2022). Further studies will be required in both mice and fish to determine to what extent Tie signalling affects LEC specification, proliferation, and survival.…”
Section: Discussionsupporting
confidence: 70%
“…Tie1 mutant mice do not show any vascular defects until E13.5 and die from haemorrhages between E13.5 and P0, but display swellings at E12.5 caused by lymphatic malformations that precede the haemorrhaging (D'Amico et al, 2010;Puri et al, 1995;Sato et al, 1995). Additionally, postnatal Tie1 deletion causes impaired lymphatic capillary network development (Korhonen et al, 2022). We here show that tie1 mutant zebrafish embryos display severe lymphatic defects in the head and trunk vasculature, in addition to the previously reported cardiac and blood vascular phenotypes including impaired brain angiogenesis, reduced CCV width, and impaired caudal vein plexus formation (Carlantoni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TIE1 and TIE2 are differentially required during the blood vascular and lymphatic network formation [9, 15, 38]. Recent studies have shown that TIE1 plays important roles in the regulation of blood vascular growth [16-18], in addition to its requirement in the formation of collecting lymphatics [12, 15, 36, 39]. TIE2 is required for the formation and maturation of blood vascular network, especially in vein development [3, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Angpt2 deletion mice were generated by CRISPR/Cas9-based genome editing. 33 36 The CRISPR guideRNA was designed with a guideRNA tool (Crispr.mit.edu, ACTGAGTCGTCGTAGTCGAG). Based on that analysis, CRISPR RNA (crRNA), trans-activating CRISPR RNA (tracrRNA), and Cas9 protein (Cas9 nuclease) were ordered from Integrated DNA Technologies (Coralville, IA, USA).…”
Section: Methodsmentioning
confidence: 99%